Antibody functionalized magnetic nanoparticles for circulating tumor cells detection and capture using magnetophoresis. (March 2019) - Burinaru, T A; Volmer, M; Avram, M; Țucureanu, V; Avram, A; Țîncu, B; Mărculescu, C; Matei, A; Marinescu, R; Militaru, M
Abstract: Circulating tumor cells (CTCs) are cells present in the blood stream during the metastasis process. They can originate from primary or secondary tumors. Circulating tumor cells can be used for early diagnosis or they can be used for prognosis evaluation and even treatment efficiency evaluation. Circulating tumor cells can be captured based on specific antigens found on their surface that differ from those of normal blood cells, they can be captured using specific electrical signatures using dielectrophoresis and they can also be captured using induced magnetic properties and magnetophoresis. In this paper we describe a method for synthesizing and functionalizing superparamagnetic nanoparticles. The nanoparticles will be covered with polyethylenglicol (PEG) molecules to reduce agglomeration and non-specific cell adhesion or blood proteins fouling. The PEG covered magnetic nanoparticles will be functionalized with anti-EpCAM antibodies that are going to make the nanoparticles specifically bind to CTCs present in the blood sample. The samples will be further processed in a microfluidic device that will separate the targeted cells through magnetophoresis.